EFFECT OF CIDR AND PGF 2a TO IMPROVE THE CONCEPTION RATE IN HOLSTEIN FRIESIAN CROSSBRED HEIFERS - VIJAYARAJAN, A; MEENAKSHISUNDARAM, S (The Indian Journal of Animal Reproduction, 2023)
The objective was to evaluate the efficacy of an intravaginal progesterone insert and injection of PGF2"' forsynchronizing estrus in Holstein Friesian heifers under field condition. The heifers were divided into two groupseach consisting of eighteen (n=18) animals. Group I animals served as control and Group II animals were treatedwith an intra vaginal P4 device {CIDR) for 9 days and PGF2o: was given intramuscularly 24 hrs prior to CIDRremoval. Fixed time artificial insemination was carried outat48 and 72 hrs after Cl DR removal. The overall conceptionrates obtained was 33.33 % in group I animals and 77. 77 % in group II animals treated with CIDR and PGF2alpha.
Keywords: CIDR; PGF2alpha; Conception Rate; Holstein; Friesian crossbred heifer